What about us? Teachers’ participation in schools’ strategic action plans - Carvalho, Marisa (2021)
Schools in various parts of the world adopt plans or projects to improve the quality of school processes and students’ learning. Therefore, it is important to understand the processes of strategic planning such as teachers’ participation on decision making related to school plans. Apparently a limited number of studies have hitherto been conducted on teachers’ participation in strategic planning. The purpose of this paper is to examine teachers’ participation in decision making and strategic action planning in Portuguese schools. A survey employing self-administered scales was taken. Teachers' participation, other stakeholders’ participation, planning, and decision making, professional development, plans’ importance and validation, and ownership were the dimensions considered. Data were collected from 804 Portuguese teachers. Participants reported moderate to high levels of participation in strategic action plans, but they also reported moderate to low levels of participation in overall school decisions, plans’ importance and validation, sense of ownership and recognition of relevant opportunities for professional development. These results indicate that participation and collaboration are essential determinants of plan and action success in educational contexts. The participative nature of decision making and strategic planning seems to underscore the relevance, value and adequacy of schools’ plans from the perspective of teachers. However, differences in these dimensions related to teachers’ experience and professional roles also point to lower levels of participation from some teachers, which may hinder their involvement in school actions and improvement. This study suggests the need to explore the dominant types of participation and collaboration in Portuguese schools and to analyse the importance of other variables.